PERAN KOMPETENSI SOSIAL GURU PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH NEGERI KEMANTAN KABUPATEN KERINCI - Masnur Alam (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2018)
Islamic Education teachers' social competence is still questionable and has not been done optimally and needs to be improved. The aims of this research are to find out how the role of social competence of the Islamic Education teachers' of Kemantan State Islamic School should be owned. Data and information are obtained from primary and secondary data from observations and interviews with Islamic Education teachers, as well as literature related to the focus of the study. The results of the study show that communication with Madrasah heads is generally good, but has not been done routinely. Communication with fellow teachers is still limited to subject group teachers. Communication with students has gone well, but is still oral and has not used communication in writing in the form of dictates / papers and electronic media. Communication with parents / guardians is still limited to parents living around madrasah. And communication with the community is still limited to madrasah committees and communities in their respective homes, and has not conducted research in the community.